2016
DOI: 10.1177/0741713616669588
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Profiles of Adult Learners

Abstract: This study investigated profiles of autonomous and controlled motivation and their effects in a sample of 188 adult learners from two Portuguese urban areas. Using a person-centered approach, results of cluster analysis and multivariate analysis of covariance revealed four motivational groups with different effects in self-efficacy, engagement, and learning. The study showed that groups of learners who have high autonomous motivation in the beginning of a course score higher in self-efficacy and later on in be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
0
13

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(74 citation statements)
references
References 43 publications
5
56
0
13
Order By: Relevance
“…We located mainly empirical studies of both quantitative and qualitative methods as well as literature reviews from international sources. We found that six teaching strategies were consistently linked to increased motivation among adult learners: providing relevance, addressing settlement needs, incorporating life experiences, encouraging learner autonomy, promoting collaborative learning and building self-efficacy (Fenwick 2004;Norton and Toohey 2011;Po-ying 2007;Rothes, Lemos and Gonçalves 2017;Seaton 2018;Windisch 2016; Zarei and Zarei 2015). These six strategies became our focus.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We located mainly empirical studies of both quantitative and qualitative methods as well as literature reviews from international sources. We found that six teaching strategies were consistently linked to increased motivation among adult learners: providing relevance, addressing settlement needs, incorporating life experiences, encouraging learner autonomy, promoting collaborative learning and building self-efficacy (Fenwick 2004;Norton and Toohey 2011;Po-ying 2007;Rothes, Lemos and Gonçalves 2017;Seaton 2018;Windisch 2016; Zarei and Zarei 2015). These six strategies became our focus.…”
Section: Methodsmentioning
confidence: 99%
“…LINC students learn language through content, such as shopping, going to the doctor and employment. Similarly, there exists a strong positive correlation between classroom use of employment-related topics and the participation of adults with limited education (Rothes et al 2017). The need for a work-related curriculum is so great that the federal and provincial Canadian governments are focusing on literacy and employment where learners can earn certificates such as first aid or work safety, while building their language skills.…”
Section: Settlement Needsmentioning
confidence: 99%
“…Recently, an increasing number of studies have adopted person-centered approaches in response to calls to investigate naturally occurring multiple motivational profiles in face-to-face settings (eg, Corpus & Wormington, 2014;Linnenbrink-Garcia et al, 2018). In general, these studies identified two sets of categorizations, one with four clusters (or profiles) (eg, Rothes, Lemos, & Gonçalves, 2017;Wormington, Corpus, & Anderson, 2012) and the other with three (Ratelle et al, 2007). The former consists of a good quality profile (ie, high autonomous and low controlled motivation), a poor quality profile (ie, low autonomous and high controlled motivation), a high-quantity profile (ie, high autonomous and high controlled motivation) and a low-quantity profile (ie, low autonomous and low controlled motivation).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some studies have reported that the face-to-face learning performance was inferior among learners with high-quantity profiles, as compared to those with good quality profiles (Corpus & Wormington, 2014;Hayenga & Corpus, 2010;Liu et al, 2009;Vansteenkiste et al, 2009). Others have suggested that the learning of students with high-quantity motivational profiles was as adaptive as that of their good-quality counterparts (ie, Rothes et al, 2017;Wormington et al, 2012). Wormington et al hypothesized that controlled motivation may become more adaptive in highly controlled settings such as high school than in other educational settings where intrinsic engagement is valued more highly.…”
Section: Motivational Profiles and Learning Outcomesmentioning
confidence: 99%
“…They enroll voluntarily in educational programs and are usually part-time students who have to balance education with other life tasks like work and family, which means that they are often more at risk of dropping out from education and training [52]. Gaining independence and confidence can help to develop self-directedness in learning [34].…”
Section: Professional Practicementioning
confidence: 99%